Characterization of oil from liver and visceral fats of patin (Pangasianodon hypophthalmus Sauvage) and its use in hand cream preparation - Shabanikakroodi, Samana (2014)
The visceral fat and liver of patin, Pangasianodon hypophthalmus, are considered as waste from fish processing. Converting these byproducts into fish oil not only provide a good source of health promoting fatty acids but also can be used for the production of value added products. The proximate and fatty acid compositions of the visceral storage fat and liver of patin were determined. Fat content of the visceral fatty tissue of female and male patin were 77.64 and 73.23%, respectively, whereas fat content of the liver of female and male were 11.71 and 9.59%, respectively. The total amounts of monounsaturated and polyunsaturated fatty acids of the liver of female and male catfish were 51.03 and 50.55 %, respectively, whereas in fatty tissue of female and male were 50.46 and 50.31%, respectively. Refining was done on the extracted oil from byproducts of patin to produce a more pure and stable product. The effect of refining procedure on the fatty acid composition of oil from various refining steps and the quality of the final product were investigated. Fatty acids found in crude and refined patin oil were C12:0, C14:0, C14:1, C16:0, C16:1, C18:0, C18:1, C18:2, C18:3, C18:4, C20:0, C20:1, C20:4, C20:5, and C22:6. The amount of saturated fatty acids of refined oil were significantly (P < 0.05) higher than that of crude oil. The total amounts of monounsaturated fatty acids of oil from different refining steps were not significantly (P > 0.05) different, whereas the total amount of polyunsaturated fatty acids of refined oil was significantly (P < 0.05) lower than that of crude oil. The eicosapentaenoic acid, docosahexaenoic acid, and n-3 to n-6 ratio of refined oil were 0.83, 0.79%, and 1.01, respectively. Analysis of the physical and chemical properties of refined oil indicated the suitability of patin oil to be used in the formulation of hand cream. In the present study, the efficacy and stability of various hand cream formulations using 0, 1.0, 2.5 and 5.0% of fish oil were investigated and compared. The appearance, odor, texture, and pH of formulations containing 1 and 2.5% of fish oil remained stable in very good qualities during the storage, whereas the related values to the appearance and texture of formulation containing 5.0% of fish oil at the end of 6 months of storage at 45°C were significantly (P < 0.05) lower than other formulations and previous evaluations of this formulation. Weight loss and microbial contamination were not observed in all formulations under study. Efficacy of preservative system was proved through preservative challenge tests. Efficacy test indicated that the formulations containing fish oil were preferred by volunteers rather than the one without the fish oil. Addition of fish oil significantly (P < 0.05) increased the moisturizing effects of hand creams. The formulation containing 2.5% of fish oil obtained the best related values in all investigated items including skin texture, moisture, smoothness, brightness, and well being perception.